2018
DOI: 10.3389/fpsyg.2018.01754
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Task-Related Functional Connectivity Changes Predict Reading Development

Abstract: Longitudinal studies suggest developmentally dependent changes in lexical processing during reading development, implying a change in inter-regional functional connectivity over this period. The current study used functional magnetic resonance imaging (fMRI) to explore developmental changes in functional connectivity across multiple runs of a rhyming judgment task in young readers (8–14 years) over an average 2.5-year span. Changes in functional segregation are correlated with and predict changes in the skill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
(56 reference statements)
1
14
0
Order By: Relevance
“…Co-activation in the left STG during speech and print processing also differentiated young readers from pre-readers and correlated with reading performance in Polish six-year olds 70 . Improvement of reading skills over time was also predicted by changes in the functional connectivity patterns within the reading network, with stronger connections between STG and IFG during a written word rhyming task 71 . Moreover, in the phonological task the functional connection strength at the pre-reading stage between the left IPC, left IFG, left vOT, and right angular gyrus predicted later reading development 49 .…”
Section: Neural Precursors Of Readingmentioning
confidence: 94%
“…Co-activation in the left STG during speech and print processing also differentiated young readers from pre-readers and correlated with reading performance in Polish six-year olds 70 . Improvement of reading skills over time was also predicted by changes in the functional connectivity patterns within the reading network, with stronger connections between STG and IFG during a written word rhyming task 71 . Moreover, in the phonological task the functional connection strength at the pre-reading stage between the left IPC, left IFG, left vOT, and right angular gyrus predicted later reading development 49 .…”
Section: Neural Precursors Of Readingmentioning
confidence: 94%
“…First, this task requires access to letter-sound mapping rules in order to pronounce the stimuli, and prevents using basic visual memory of known words as an aid to word identification. Second, past and ongoing studies of typically developing children [9, 64] have found that developmental changes in PDE scores are predicted by changes in connectivity over the same period. Because the classification of reading and other learning difficulties may be the subject of disagreement, the remaining standardized measures provide quantifiable support for our participants as a sample of children with reading difficulty.…”
Section: Methodsmentioning
confidence: 99%
“…Much of this research has focused on behavioral predictors, such as performance on various standardized measures. However, researchers within the last few decades have begun to extend this work by exploring the use of language-related brain-based predictors (e.g., Lee et al, 2016;Linkersdorfer et al, 2014;McNorgan et al, 2011;Preston et al, 2016;Smith et al, 2018). A subset of this research, which has examined the use of both behavioral and neural predictors, has shown that both functional-and structural-based neural measures explain unique variance in reading growth over that of purely behavioral measures (e.g., Bach et al, 2013;Hoeft et al, 2007;Hoeft et al, 2011;Maurer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%